PREFERENCES FOR RECEIVING AN EVIDENCE-BASED JOB RETENTION PROGRAM AMONG ADULTS WITH ARTHRITIS. (11th November 2018) - Simpson, L; Keysor, J; Cochrane, F; Allaire, S
Abstract: Persons with chronic musculoskeletal conditions such as arthritis or back pain experience high rates of employment cessation impacting retirement, health, and quality of life in late life years. Indeed, up to 1/3 of people with arthritis are unemployed within 10 years of initial diagnosis. Few if any evidence-based programs are available to help adults at risk of job loss remain employed. In a recent clinical trial, the Work It Program, a brief educational program to identify and solve work-related barriers delivered by physical and occupational therapists was effective at preventing job loss. The most effective means to deliver this type of intervention is not known. Thus, the purpose of this study was to explore how people in the Work It Study (N=31) would like to receive this type of evidence-based program. This qualitative study used a guided open ended question process to collect data and content analysis to analyze the data. Three themes emerged: 1) participants wanted to learn about the program from trusted sources, 2) participants wanted to receive the intervention from trusted sources, and 3) participants wanted to receive the program in a familiar and comfortable setting. Participants noted preferences across three settings: i) health care, ii) employment-based, and iii) community-based.